PSP-demonstratie tegen MLF/NAVO. Spandoek met teksr 'MLF? Neen! Volledige kernstop? Ja!' - Meerendonk, Ben van,
PSP-demonstratie tegen MLF/NAVO. Spandoek met teksr 'MLF? Neen! Volledige kernstop? Ja!'.